2012
DOI: 10.1039/c2cp23501c
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adsorbed polar molecules on the electronic transport in a composite material Li1.1V3O8–PMMA for lithium batteries

Abstract: The broadband dielectric spectroscopy (BDS) technique (40 to 10(10) Hz) is used here to measure the electronic transport across all observed size scales of a Li(1.1)V(3)O(8)-polymer-gel composite material for lithium batteries. Different electrical relaxations are evidenced, resulting from the polarizations at the different scales of the architecture: (i) atomic lattice (small-polaron hopping), (ii) particles, (iii) clusters of particles, and finally (iv) sample-current collector interface. A very good agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…1, since they are constituted of clusters (aggregates) of particles and particles separated by resistive and capacitive barriers that limit the charge diffusion in the whole material. [17][18][19][20][21][22] Moreover the electronic connectivity is reduced because the electrode materials are porous, which diminishes contact surface between the clusters and between the particles inside the clusters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, since they are constituted of clusters (aggregates) of particles and particles separated by resistive and capacitive barriers that limit the charge diffusion in the whole material. [17][18][19][20][21][22] Moreover the electronic connectivity is reduced because the electrode materials are porous, which diminishes contact surface between the clusters and between the particles inside the clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the electronic connectivity is reduced because the electrode materials are porous which diminishes contact surface between the clusters and between the particles inside the clusters. [17][18][19][20][21][22] It has been previously shown that Broadband Dielectric Spectroscopy (BDS) is much more suitable to describe the electronic transport in electrode materials for lithium batteries. The response of a material submitted to a timedependent electric field can be described by the time-dependent current density or by the time-dependent polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a similar phenomenon was reported on laminar silica-polymer composite dielectrics 52 and Li 1.1 V 3 O 8 particles. 53 Surprisingly enough, in the case of LFPC-EB-2L (Fig. 6), although the sample conductivity is much lower, it appears nearly independent of temperature.…”
Section: Electronic Transport Properties Of Solvent and Functionalize...mentioning
confidence: 87%
“…The broadband dielectric spectroscopy (hereafter called BDS) allows the study of the electronic conductivity of a composite electrode at all the scales of its architecture (from interatomic distances to macroscopic lengths) as function of the temperature usually between 200 and 400 K [1][2][3][4][5]. This technique thus allows the clarification of the charge transport mechanisms and the origin of the limitations in these mechanisms, depending on the composition, processing and morphology of the composite electrode.…”
Section: Introductionmentioning
confidence: 99%
“…In the first case, the influence of surface ageing and degradation is considered and in the second one, the influence of a carbon coating is analysed. Moreover, the nature of the electronic transfer in composite electrode based on the Li1.1V3O8 active material is investigated [4]. Permittivity and conductivity measurements have been recorded in a wide frequency range from 10 Hz to 10 GHz in the temperature range 200 to 300 K.…”
Section: Introductionmentioning
confidence: 99%